Virtual Reality Based on Social Cognitive Theory for Type 2 Diabetes Management in Indonesia - Herlina Jusuf; Zainuddin; Hartono Hadjarati; Fransiskus Xaverius Widiantoro; Wahyudin; Rizqi Yanuar Pauzi; Sarinah Basri K (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2026)
Introduction: Diabetes has become a significant global health problem, particularly burdening low-income countries economically. Innovative and integrated digital solutions can help reduce the impact of diabetes and improve the quality of care. However, virtual reality (VR) digital solutions have never been applied in Gorontalo. This study aims to demonstrate the novel integrated effect of diabetes health literacy, self-efficacy, physical activity, and HbA1c blood sugar control. Methods: A quasi-experimental study with two intervention groups was conducted in Indonesian from October to December 2024. For the first time, researchers trained the intervention group to use virtual reality. Results: This study demonstrated that both intervention groups, Virtual Reality (VR) and WhatsApp (WA), showed significant improvements in knowledge (p < 0.0001) and self-efficacy (p < 0.0001) post-intervention. Physical activity also significantly increased in both groups (p < 0.0001). Moreover, a significant reduction in HbA1c levels was observed in the VR group (median reduction 1.36%, p = 0.0005) and the WA group (mean reduction 0.67%, p = 0.0002). Comparatively, VR was more effective in improving self-efficacy (Post-VR median = 58.00 vs. Post-WA = 54.00; p < 0.0001), while WA was more effective in increasing physical activity (Post-WA median = 1824 MET-minutes/week vs. Post-VR = 953.3 MET-minutes/week; p = 0.0006) and reducing HbA1c levels (Post-WA median = 9.05% vs. Post-VR = 10.70%; p = 0.0049). No significant difference was found between groups in knowledge improvement. Conclusion: As this intervention yielded significant improvements in self-management among T2DM patients, researchers recommend that policy-makers replicate this intervention as a national program and promote increased use of digital devices (VR) to enhance health literacy, self-efficacy, physical activity, and clinical outcomes (HbA1c) in T2DM management.